Enhanced heat transfer efficiency in Williamson Radiated hybrid nanofluid over a porous Surface: Role of activation energy, chemical reaction and motile Microbes - Muhammad Umar Farooq; Aaqib Majeed; Parvez Ali; Taoufik Saidani (Case Studies in Thermal Engineering)
The present study delves into the complex dynamics of three-dimensional Williamson hybrid nanofluid flow, comprising Zn–SiO2/H2O, over a porous, rotating stretching sheet under the influence of thermal radiation and heat generation. The analysis is further enriched by incorporating the effects of activation energy, velocity slip, and motile microorganisms, capturing the bio-convective and reactive nature of the system. Water (H2O) serves as the base fluid, augmented with zinc (Zn) and silicon dioxide (SiO2) nanoparticles to enhance thermal performance. This model directly relates to advanced energy and heat management systems, such as solar thermal collectors and compact electronic cooling devices, where non-Newtonian behavior and hybrid nanoparticle suspensions significantly influence flow stability and heat transfer rates. The governing coupled nonlinear partial differential equations (PDEs) are reduced to a system of nonlinear ordinary differential equations (ODEs) through similarity transformations. These equations are then numerically solved using MATLAB bvp4c solver, employing a robust finite difference scheme for accuracy and stability. Validation of the results against existing literature confirms the model's reliability. Detailed graphical analysis highlights the impact of pertinent parameters, including the Williamson parameter, Prandtl number, magnetic and rotational parameters, Forchheimer coefficient, radiation and porosity parameters, Lewis and bioconvection Lewis numbers, chemical reaction rate, activation energy, and Peclet number, on velocity, temperature, concentration, and motile microorganism distributions. Key findings indicate that an increase in the magnetic parameter suppresses fluid velocity, while enhancement is noted in the concentration profile against the rotational parameter. Additionally, higher Lewis and Peclet numbers are observed to reduce the density of motile microorganisms. These insights establish a strong foundation for optimizing hybrid nanofluid-based cooling and energy systems, offering enhanced thermal conductivity and performance in cutting-edge technological applications.